The Effect of E-Service Quality and Perceived Price Fairness on Customer Loyalty Which Customer Satisfaction as Intervening Study on Online Shopping Site in Indonesia - Olivia Citra Octaviani; Mohamad Rizan; Agung Kresnamurti Rivai P (LPPM Universitas Negeri Jakarta, 2021)
This study examines the effect of e-service quality and perceived price fairness on customer loyalty with the intervening role of customers’ satisfaction in the online shopping site in Indonesia. The research method uses a quantitative research design with a survey model. The sample used in this study is Lazada consumers which consists of five large cities in Indonesia (Jakarta, Bogor, Depok, Tanggerang, and Bekasi City) and have done online shopping site at Lazada at least once in the last six months. The object of this research were the 200 customer respondents who had made purchases on the largest online shopping site platform of Indonesia, Lazada. Data analysis was done by using SPSS and Structural Equation Modeling (SEM). The results show that: first, the e-service quality and perceived price fairness affect customer satisfaction positively. Second, there is a mediating effect of customer satisfaction on the relationship between e-service quality and perceived price fairness on customer loyalty. Third, e-service quality and perceived price fairness directly affect customer loyalty positively but insignificantly. The result implies that the role of customer satisfaction is significant in creating loyalty. In the online shopping site a good quality and perception about price could positively influence customers but not necessarily form loyalty.